A Genome-Wide Survey for Arabidopsis Leucine-Rich Repeat Receptor Kinases Implicated in Plant Immunity - Kemmerling, Birgit; Halter, Thierry; Mazzotta, Sara; Mosher, Stephen; Nürnberger, Thorsten (Frontiers in Plant Science, 2011)
Receptor-like kinases (RLK) are among the largest gene families encoded by plant genomes. Common structural features of plant RLKs are an extracellular ligand binding domain, a membrane spanning domain and an intracellular protein kinase domain. The largest subfamily of plant RLKs is characterized by extracellular leucine-rich repeat structures (LRR-RLK) that are known biochemical modules for mediating ligand binding and protein-protein interactions. In the frame of the Arabidopsis Functional Genomics Network (AFGN) initiative of the German Research Foundation (DFG) we have conducted a comprehensive survey for and functional characterization of LRR-RLKs potentially implicated in Arabidopsis thaliana immunity to microbial infection. Arabidopsis gene expression patterns suggested an important role of this class of proteins in biotic stress adaptation. Detailed biochemical and physiological characterization of the brassinosteroid insensitive 1 (BRI1)-associated receptor kinase 1 (BAK1) revealed brassinolide-independent roles of this protein in plant immunity, in addition to its well-established function in plant development. The LRR-RLK BAK1 has further been shown to form heteromeric complexes with various other LRR-RLKs in a ligand-dependent manner, suggesting a role as adapter or co-receptor in plant receptor complexes. Here, we review the current status of BAK1 and BAK1-interacting LRR-RLKs in plant immunity.